Ruby Gillman, teenage kraken [videorecording (DVD)] - Brady, Pam; Brown, Brian C. (Screenwriter); DiGuiseppi, Elliott (Universal, 2023)
Sweet, awkward sixteen-year-old Ruby Gillman is desperate to fit in at Oceanside High, but she mostly just feels invisible. She's math-tutoring her skater-boy crush, who only seems to admire her for her fractals, and she's prevented from hanging out with the cool kids at the beach because her over-protective supermom, has forbade Ruby from ever getting in the water. But when she breaks her mom's #1 rule, Ruby will discover that she is a direct descendant of the warrior Kraken queens and is destined to inherit the throne from her commanding grandmother, the Warrior Queen of the Seven Seas. The Kraken is sworn to protect the oceans of the world against the vain, power-hungry mermaids who have been battling with the Kraken for eons. There's one major, and immediate, problem with that: The school's beautiful, popular new girl, Chelsea just happens to be a mermaid. Ruby will ultimately need to embrace who she is and go big to protect those she loves most.